OPTIMIZATION OF THE CAPACITY FACTOR OF ENERGY SHIPS FOR FAR-OFFSHORE WIND ENERGY CONVERSION USING WEATHER-ROUTING - Roshamida Abd Jamil (Tesis, 2022)
A key advantage of the energy ship is that it is mobile. Therefore, its trajectory can be optimized using weather-routing in order to maximize energy production, which is focus o this thesis. The analysis in the thesis is based on numerical simulations.